Can an app Help Identify Psychomotor Function Impairments during Drinking Occasions in the Real World? A Mixed-Method Pilot Study. Issue 4 (October 2017) - Suffoletto, Brian; Goyal, Akash; Puyana, Juan Carlos; Chung, Tammy
Background: Being able to measure the acute effects of alcohol consumption on psychomotor functions in natural settings could be useful in injury prevention interventions. This study examined the feasibility and acceptability of collecting app-based measures of information processing, working memory, and gait stability during times of typical alcohol consumption among young adults. Methods: Ten young adults (aged 21–26) with hazardous drinking completed a baseline assessment and ecological momentary assessments (EMA) on 4 consecutive Fridays and Saturdays, every hour from 8pm to 12am . EMA assessed alcohol consumption and perceived intoxication, followed by a digit symbol substitution task (DSST), a visuospatial working memory task (VSWMT), and a 5-step tandem gait task (TGT). Exit interviews probed user experiences. Multilevel models explored relationships between estimated blood alcohol concentration (eBAC; mg/dL) and DSST and VSWMT performance. Results: Participants completed 32% of EMA. Higher rates of noninitiation occurred later in the evening and over time. In multilevel models, higher eBAC was associated with lower DSST scores. Eight out of 10 individuals had at least 1 drinking occasion when they did not perceive any intoxication. Lower DSST scores would identify impairment in 45% of these occasions. Exit interviews indicated that adding real-time feedback on task performance could increase awareness of alcohol effects. Conclusions: Collecting app-based psychomotor performance data from young adults during drinking occasions is feasible and acceptable, but strategies to reduce barriers to task initiation are needed. Mobile DSST is sensitive to eBAC levels and could identify occasions when an individual may not perceive impairments.